ESTIMATING THE EFFICIENCY OF CONTROL OVER CATERING ENTERPRISES IN NIZHNIY NOVGOROD (Russian Journal of Economics and Law)
Objective: to identify and systematize the most problematic objects of control in various cafes of Nizhny Novgorod, in the opinion of their leaders, and to offer measures for their improvement.Methods: the study is based on questionnaires, analysis, and logical classification.Results: the results of the respondents’ polling are described; just under a third of respondents indicated that one of the last two inspections is the identification of cases of poisoning in the catering industry; the main object of control, of the most commonly detected defects, is visual inspec- tion. When conducting internal monitoring, the main object with the majority of defects, according to respondents, is the safety analysis. Then, about the same number of respondents indicated the processes such as medical examination of personnel and timely informing of the authorities.The factor causing the greatest concern during the control, according to the managers, is the poor hygiene of the cooks, while the less significant factor, according to respondents, is the violation of the control procedure.Most problems can be solved through the availability of a highly qualified staff, the frequency of violations will be minimized. The result of solving a problem should be the creation of unified program of personnel training/retraining, aimed not only at increasing knowledge, but also at the process of developing such qualities as self-control and self-organization.Scientific novelty: on the basis of the study, it is concluded, in which direction it is necessary to improve the control activity in the sphere of public catering.Practical significance: the main provisions and conclusions of the article can be used in the design and implementation of new standards regulating activities to control the public catering.